2022
DOI: 10.1259/dmfr.20210272
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based observation of the size and morphology of temporomandibular joint articular disc and condyle in young asymptomatic adults

Abstract: Objective: To investigate the size and morphology of the temporomandibular joint (TMJ) articular disc and condyle in young asymptomatic adults by using magnetic resonance imaging (MRI) and to provide a reference for clinical diagnosis and scientific study of temporomandibular disorders (TMD). Methods: Overall, 93 undergraduate volunteers without TMD were enrolled from the freshmen pool at the Qingdao University. All participants underwent MRI of the oblique sagittal and oblique coronal TMJ planes. The articula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…And, Hosgor et al [ 9 ] reported joint effusion increased in direct proportion to the severity of pain and disc displacement. In terms of gender, Luo et al [ 10 ] investigated the size and morphology of articular disc and condyle in young asymptomatic adults and found the thickness of the anterior band of the disc and the media-lateral dimensions of the condylar head were gender-related. On the contrary, Demir et al [ 11 ] compared TMD patients' complaints, clinician's examination findings, and MRI findings by considering gender and found no significant difference.…”
Section: Introductionmentioning
confidence: 99%
“…And, Hosgor et al [ 9 ] reported joint effusion increased in direct proportion to the severity of pain and disc displacement. In terms of gender, Luo et al [ 10 ] investigated the size and morphology of articular disc and condyle in young asymptomatic adults and found the thickness of the anterior band of the disc and the media-lateral dimensions of the condylar head were gender-related. On the contrary, Demir et al [ 11 ] compared TMD patients' complaints, clinician's examination findings, and MRI findings by considering gender and found no significant difference.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, only these four articular disk shapes were found, with the proportions not differing significantly between the CMO, CMC, and CMOC and HC groups. In a previous study, the condylar morphology was divided into round, flattened, and beak-like shapes, with most asymptomatic volunteers showing a round condyle ( Luo, Qiu, et al, 2022a ). Since the condylar shape is closely related to condylar function, the condylar morphology in TMDs differs among patients ( Katsavrias and Halazonetis, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…The articular disk and condylar morphologies were determined in the oblique sagittal plane (Luo, Qiu, et al, 2022a). The articular disk morphology was divided into six categories: biconcave, Frontiers in Bioengineering and Biotechnology frontiersin.org thickening posterior, thickening anterior, biplanar, biconvex, and folded (Figure 2E).…”
Section: Tmj Structure On Mri Scansmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical assessment is only qualitative. Attempts have been made to assess TMJ with surface electromyography [ 2 ], cone beam computed tomography [ 8 , 9 ] and magnetic resonance imaging (MRI) [ 10 , 11 , 12 ]. Therefore, we propose a quantitative method based on biexponential T2 maps for the analysis of the relationship between disk displacement and other stomatognathic structures.…”
Section: Introductionmentioning
confidence: 99%